Pemanfaatan Media Pembelajaran Berbasis ICT Dalam Pengembangan Kompetensi Profesional Guru Pendidikan Agama Islam - Pramesti, Iftitah Ardiwira; Faujiyah, Nur; Rahmawati, Putri; Hamid, Abdulloh; Hafiyusholeh, Moh. (LP2M IAIN kUDUS, 2023)
This research aims to investigate the utilization of Information and Communication Technology (ICT)-based learning media in enhancing the professionalism of Islamic Religious Education teachers. ICT-based learning media offers significant potential for Islamic Religious Education teachers to expand access to learning resources, create interactive learning experiences, boost student motivation, and foster collaboration among fellow educators. This study proposes a descriptive-quantitative research approach, involving the distribution of questionnaires to Islamic Religious Education teachers in the Candi sub-district of Sidoarjo. Through this research, it is anticipated that a deeper understanding of the impact and implications of utilizing ICT-based learning media on the professional development of Islamic Religious Education teachers will be gained. Based on the analyzed data, the research will demonstrate that out of the surveyed teachers, 16 teachers (53.33%) achieved high scores, while 11 teachers (36.67%) fall into the medium category, and finally, 3 teachers (10%) fall into the low category. This research also conducted interviews with several Islamic Religious Education teachers at the middle school level, revealing that these teachers have effectively utilized ICT-based media in their teaching and professional development.